The actual approach of sentinel node biopsy in cutaneous melanoma - Maria Szymaniak; Julia A. Janecka; Wiktor Grabek; Jan Radomski; Kinga Flisiewicz-Wysocka; Karolina Mizera; Mateusz Wichtowski (Nowotwory)
Sentinel lymph node biopsy (SLNB) is a well-established standard of care in melanoma treatment, but its role is evolving.Before the advent of modern systemic therapies, SLNB was critical in identifying which patients would benefit fromcomplementary lymphadenectomy and which would not require this procedure. Currently, after a positive sentinel node biopsy, lymphadenectomy is no longer performed, altering the procedure’ssignificance. The SLNB identifies patients who will benefit from adjuvant treatment. Additionally, it enhances controlover locoregional lymphatic flow. As for now, there is no alternative to sentinel node biopsy. The gold standard for marking sentinel nodes in melanoma remains the dual radioisotope-dye method, using lymphoscintigraphyand SPECT-CT. There is ongoing research for new tracers that might replace this method, likely ferromagnetic tracers, which have shownnon-inferiority in breast cancer, have not yet proven to be of comparable value in melanoma, due to unpredictablelymphatic drainage, which required preoperative imaging.